Experimental and Theoretical Approaches to Actinide Chemistry : From Fundamental Systems to Practical Applications. - Gibson, John K. (John Wiley & Sons, Incorporated, 2018)
A review of contemporary actinide research that focuses on new advances in experiment and theory, and the interplay between these two realms Experimental and Theoretical Approaches to Actinide Chemistry offers a comprehensive review of the key aspects of actinide research.